The morphological profile and specific physiological parameters of the Bushmen in Eastern Bushmanland - Reavell, Rebecca Joanna (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Human Movement Studies) -- University of Stellenbosch, 1994.